The kindness curriculum : introducing young children to loving values - Rice, Judith, 1953- (Beltsville, MD : Distributed by Gryphon House, 1995)
Contains instructions for activities designed to reinforce the concepts of kindness, covering love, empathy, gentleness, respect, visualization, self-control, friendship, and conflict resolution.
Includes bibliographical references (p. 121-122).
Professional
Keywords: Early childhood education -- Activity programs; Moral education (Early childhood); Social values -- Study and teaching (Early childhood); Early childhood education; Moral education; Social values -- Study and teaching